Process development for laser-based additive manufacturing of solid oxide fuel cells - Tan, Kenneth Hong Yi (2019)
Solid oxide fuel cells (SOFCs) are electrochemical conversion devices which directly convert chemical energy of the fuel into electrical energy with high efficiency. SOFC comprises of an anode, electrolyte and cathode layer that are fabricated individually upon each other, usually one at a time. Additive manufacturing (AM) is a new fabrication technique that utilizes a layer by layer fabrication technique, which can potentially be suitable for use in SOFC, since it is also building different materials in a layer-wise manner. Furthermore, the use of laser-based AM techniques can eliminate the issue of long sintering hours by directly densifying the materials using laser as the heat source. In addition, SOFCs possessing newer designs can be fabricated with ease using this technique, gradient-structure electrodes can also be created either by design or varying the laser parameter and material composition. Therefore, this thesis aims to develop a process as well as study the feasibility for fabricating SOFC using laser-based AM techniques. First, a step-by-step process was conducted to identify significant factors affecting the building of Nickel metal support structures using Selective Laser Melting (SLM) process. Laser power, scanning speed and hatch spacing were found to be the dominant factors affecting the printability of the parts. Next, a porous structure was designed and printed which acted as a metal support for SOFC. A functional cell was further built upon the metal support and the electrochemical performance was investigated. Although a low open circuit voltage (OCV) of 0.53 V was obtained with a maximum power density of 11.0 mW/cm2 from the cell, it demonstrated potential of this technique as a new fabrication process. In order to realize the fabrication of the entire SOFC by laser-based AM, the influence of laser on SOFC materials were conducted. The effect of two different laser sources, Nd:YAG fibre laser and CO2 laser was studied on NiO-YSZ anodic material, which showed that CO2 xvi laser was better absorbed by the oxide material. In addition, dendrite features were formed on the surface, which were influenced by the rapid solidification process and could be modified by adjusting laser processing parameters. Although the laser-modified SOFC did not perform as well as the conventional one, it was found that significant improvement was made on the charge transfer kinetics. Lastly, the influence of laser on YSZ electrolyte surface showed that the polarization resistance of the cell was reduced due to better oxygen adsorption/dissociation process. These experiments demonstrated that laser-based AM is a viable fabrication tool for SOFC.